Association Between Parental Feeding Styles, Body Mass Index, and Consumption of Fruits, Vegetables and Processed Foods with Mothers´ Perceptions of Feeding Difficulties in Children - De Moraes-Ferrari, G (BioMed Central Ltd, 2024)
Background: Feeding difficulties (FDs) are complex phenomena influenced by parental factors, feeding behaviour, and cultural factors. However, studies of the influences of these factors on FDs incidence are scarce. Thus, this study aimed to identify the associations between mothers’ perceptions of FDs in children and parental feeding styles, body mass index, and the consumption of fruits, vegetables and processed foods. Method: Two hundred and fifty-seven mothers of children aged 1 to 6 years and 11 months participated in this cross-sectional study and self-completed electronic questionnaires on sociographic variables, parental feeding styles, the consumption of fruits, vegetables and processed foods and FDs. Nutritional status was classified by body mass index (kg/m2). Results: The prevalence of FDs in children was 48.2%, and the mean age was 43.8 (± 17.6) months. The indulgent parental feeding style was the most common (40.1%), followed by the authoritative (31.1%), authoritarian (23.7%), and uninvolved (5.1%) styles. An indulgent parental feeding style (OR: 4.66; 95% CI: 2.20–9.85), a high body mass index (OR: 1.35; 95% CI: 1.09–1.68), and the consumption of processed foods (OR: 5.21; 95% CI: 2.85–9.53) were positively associated with increased odds of the absence of FDs in children. The associations of authoritarian and uninvolved parental feeding styles and the consumption of fruits and vegetables with FDs in children were not significant. Conclusion: This study identified multiple factors that are possibly associated with feeding behaviours in young children. However, further studies need to be undertaken to evaluate how such behaviours affect FDs. © The Author(s) 2024.